Alternate bearing across spatial scales in perennial crops: links to ecological theory and farmer resilience. - Garcia, Gabriela. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Biology.; Advisor: Colin Orians.; Committee: Elizabeth Crone, J. Micheal Reed, George Ellmore, and Laura Kuhl.; Keywords: Ecology, Agriculture, and Plant sciences.